2009
DOI: 10.3113/fai.2009.0093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extracorporeal Shock Wave Therapy on Cultured Tenocytes

Abstract: Background: Little has been reported about the biologic effect of shock waves on human normal or pathologic tendon tissue. We hypothesized that inflammatory cytokine and MMP production would be down-regulated by shock wave stimulation. . IL-6 levels were higher in the diseased tenocytes as compared with normal tenocytes (44.10 ± 16.72 versus 0.21 ± 0.55 ng/ml, (p < 0.05). IL-1 levels in normal cells increased (2.24 ± 5.02 ng/ml to 9.31 ± 6.85 ng/ml) after shock wave treatment (p = 0.04). In diseased tenocytes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 22 publications
0
28
1
1
Order By: Relevance
“…Our previous studies demonstrated that ESWT is chondroprotective in the initiation of OA changes of the knee [19,20], and induces regression or retardation of established OA changes of the knee in rats [21]. Many studies including ours reported a dose-related effect of ESWT in bone [22], tendon [23], epigastric skin flap [24], tenocyte [25], osteoarthritis of the knee [26] and cells [27]. ESWT is a new non-invasive therapeutic modality with effectiveness, convenience and safety.…”
Section: Research Papermentioning
confidence: 76%
“…Our previous studies demonstrated that ESWT is chondroprotective in the initiation of OA changes of the knee [19,20], and induces regression or retardation of established OA changes of the knee in rats [21]. Many studies including ours reported a dose-related effect of ESWT in bone [22], tendon [23], epigastric skin flap [24], tenocyte [25], osteoarthritis of the knee [26] and cells [27]. ESWT is a new non-invasive therapeutic modality with effectiveness, convenience and safety.…”
Section: Research Papermentioning
confidence: 76%
“…Nevertheless, we are not yet able to define how, in vivo, the ESWT acts on exposed tissues. They may provide mechanical and biological stimuli determining the activation of a complex network of molecules, including a large panel of cytokines and metalloproteinases 24,[35][36][37] .…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of action is not certain, but may involve direct stimulation of the healing process, production of microcavitations, neovascularization, destruction of calcium and neural effects. 13 Investigations in cultured tenocytes have found that extracorporeal shock wave therapy demonstrates downregulation of inflammatory and other adverse MMP mediators. 13 Focused extracorporeal shock wave therapy (F-ESWT) has been shown to be effective in the treatment of plantar fasciitis, Achilles tendinopathy calcific tendinitis.…”
Section: S39mentioning
confidence: 99%
“…13 Investigations in cultured tenocytes have found that extracorporeal shock wave therapy demonstrates downregulation of inflammatory and other adverse MMP mediators. 13 Focused extracorporeal shock wave therapy (F-ESWT) has been shown to be effective in the treatment of plantar fasciitis, Achilles tendinopathy calcific tendinitis. This appears to be dose dependent, with greater success seen with higher dose regimes.…”
Section: S39mentioning
confidence: 99%